Teacher's Strategy in Increasing Students' Learning Interest in Madrasah Tsanawiyah - Tunggal, Wahyu Satrio; Alamsyah, M.; Nur Rochbani, Ita Tryas (CV. Zabags Qu Publish, 2023)
In the context of the interaction of the learning process, students experience a tendency to be less motivated in learning. This study reveals efforts to increase students' interest in learning, and student learning activities, the ability of teachers to provide learning motivation and also student learning responses through lessons in class. This study aims to increase student learning interest, determine student learning activities, teacher's ability to provide interest in learning, and also determine student learning responses through classroom learning. Various strategies can be implemented by teachers through learning in class so that students are interested in learning. However, teachers are required to have creativity and innovation in creating a conducive and effective learning atmosphere.